#TITLE_ALTERNATIVE# - KALUBIS RUSTANDI (NIM 13603009), WENDA
The objectives of this final project is to analyze accidents statistics of Boeing 737-series in general and rudder system failures of Boeing 737-series in particular. The accumulation of Boeing 737 accidents reports since early 1970 is classified into statistical form. It is then analyzed to find out the general conclusion about the pattern of the Boeing 737 accidents. Failure of the Boeing 737 rudder system is a kind of the flight control system failure that have catastrophic influence (opportunity occurrences <10(-9). Several accidents involving the rudder system failures are investigated to find the common factors and the local factors across those various accidents The mechanics of the rudder system failures are then simply analyzed using the Failure Mode and Efect Analysis (FMEA), and Fault Tree Analysis (FTA) based on information gathered from the Investigation Reports, Airworthiness Directives (ADs), and Service Bulletin (SB).